Pengaruh Budgetary Goal Characteristics Terhadap Kinerja Manajerial Dengan Budaya Organisasi Dan Komitmen Organisasi Sebagai Variabel Moderating (Studi Empiris Pada Hotel-Hotel Berbintang di Sumatera Barat-Riau) - Rina Andriani (Fakultas Ekonomi Universitas Pasir Pengaraian, 2018)
This research has hotel the influence of budgetary goal characteristics to managerial performance, the influence of interaction between organizational culture (moderating variables) with the budgeting goal characteristics to managerial performance and the influence of interaction between organizational commitment (moderating variables) with budgetary goal characteristics to the managerial performance. The research has used questionnaire from 56 respondances who had com from background as food and beverage manager and rooms of high class hotels in West Sumatera and Riau region. Hyphotesis testing has done by multiple linear regression using SPSS 15,00 (Statistical Package for Social Sciences) In this research, has found that there was no influence between the budgetary goal characteristics with the managerial performance, there was no influence of interaction between the organization culture with the budgetary goal characteristics and the influence of interaction between the organizational commitment with the budgetary goal characteristics with managerial performance